The new careers : individual action and economic change - Arthur, Michael B. (Michael Bernard), 1945- (Personnel and Human Resource Management Ser., 1999)
Working from the basis that individuals are now much more mobile in their careers than during the more stable conditions of previous eras, this book examines and predicts new patterns of career development into the 21st century.